Biopelículas de microalgas y cianobacterias, pioneras en la colonización y deterioro del monumento de saqsaywaman - Cjuno Huaman, Yuri Nilton (2025)
The Parque Arqueológico Nacional de Saqsaywaman in Cusco, Peru, faces the problem of  deterioration caused by the colonization of biofilms formed mainly by microalgae and cyanobacteria. These microorganisms, along with others such as fungi and bacteria, contribute to the degradation of lithic materials by altering the cohesion of their surface particles, which represents a critical challenge for the conservation of this historically important archaeological monument. The objective of this study was to identify the microalgae and cyanobacteria present in the biofilms of the lithic structures of this monument. For this purpose, sampling was carried out in five of the most representative sites of the archaeological complex, selecting 14 strategic points. The collected samples were processed in the laboratory using BG-11 culture media to obtain describable specimens, observed with a ZEISS Lab.A1 optical microscope and the data obtained were compared with available taxonomic databases, from AlgaeBase (https://www.algaebase.org). Sixteen genera were identified between microalgae and cyanobacteria, predominantly cyanobacteria with eight genera, followed by Chlorophyta (five genera), Charophyta (one genus) and Ochrophyta (one genus).This work is the first taxonomic report of the genera of cyanobacteria and microalgae associated with biofilms in lithic structures of the Saqsaywaman monument, providing relevant information for the design of conservation strategies and management of cultural heritage.